Elements of Sakhalin Ainu Phonetics, Phonology, and Morphosyntax in Bronisław Piłsudski’s Corpus of Ainu Folklore - Elia Dal Corso (Edizioni Ca' Foscari, 2024)
In this paper the author focuses on a number of linguistic features of East Sakhalin Ainu dialects. The language data for this study comes from a collection of traditional Ainu folklore elicited in 1903‐04 and published as Materials for the Study of the Ainu Language and Folklore by Bronisław Piłsudski in 1912. The observations on phonetics, phonology, and morphosyntax will be discussed in light of more recent data coming from West Sakhalin Ainu dialects collected in the 1960s‐1970s. This will allow for a brief consideration of the dialectal differences occurring between the two dialect subgroups as well as of the possible path of language development that took place during the 60‐70 years that separate the two sources. The aim of the author is to highlight how a thorough descriptive work on old sources of an indigenous, minority language like Ainu can give to East Asian historical linguistics and to linguistic typology more generally.